Respuesta :

The required three ways of solutions are given below.

Here,
Given expression,

13=-2(y-4)+3y


Approach 1,
13 = -2 (y - 4) + 3y
13 = -2y + 8 + 3y
13 = y + 8
13 - 8 = y
5 = y

Approach 2
13 = -2 (y - 4) + 3y
13 - 3y = -2y + 8
Adding 3y both side
13 - y = +8
Subtracting 13 on both sides
-y = -5

Multiplying by -1 on both sides
y = 5

Approach 3
13 = -2 (y - 4) + 3y
transposition of the variable to left and contents to the right
2(y - 4) - 3y = -13
2y - 8 -3y = -13
-y -8 = -13
-y = -13 + 8
-y = -5
y = 5

Thus, the required three ways of solutions are given above.

Learn more about the equation here:

brainly.com/question/10413253

#SPJ1